2007
DOI: 10.1289/ehp.10334
|View full text |Cite
|
Sign up to set email alerts
|

Cord Serum Concentrations of Perfluorooctane Sulfonate (PFOS) and Perfluorooctanoate (PFOA) in Relation to Weight and Size at Birth

Abstract: BackgroundRecent studies have reported developmental toxicity among rodents dosed with perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA).ObjectivesWe examined the relationship between concentrations of PFOS and PFOA in cord serum (surrogates for in utero exposures) and gestational age, birth weight, and birth size in humans.MethodsWe conducted a hospital-based cross-sectional epidemiologic study of singleton deliveries in Baltimore, Maryland. Cord serum samples (n = 293) were analyzed for PFOS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
395
11
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(440 citation statements)
references
References 44 publications
30
395
11
4
Order By: Relevance
“…PFOS and PFOA levels were roughly the same across the maternal age groups, which is in accordance with the previous studies by Inoue et al (2004) and Apelberg et al (2007a In two previous studies, no associations between maternal BMI and maternal or cord serum PFC levels were found which are consistent with our results (Inoue et al 2004;Rylander et al 2009). Three other studies showed inverse associations between PFOS and PFOA levels and BMI in women or men (Fei et al 2007;Eriksen et al 2011;Lindh et al 2012).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…PFOS and PFOA levels were roughly the same across the maternal age groups, which is in accordance with the previous studies by Inoue et al (2004) and Apelberg et al (2007a In two previous studies, no associations between maternal BMI and maternal or cord serum PFC levels were found which are consistent with our results (Inoue et al 2004;Rylander et al 2009). Three other studies showed inverse associations between PFOS and PFOA levels and BMI in women or men (Fei et al 2007;Eriksen et al 2011;Lindh et al 2012).…”
supporting
confidence: 93%
“…PFCs have been shown to cross the placenta (Inoue et al 2004;Liu et al 2011;Gützkow et al 2012) and thus have a potential to exert a direct influence on the developing fetus (Apelberg et al 2007a;Fei et al 2007). According to previous studies, the median PFC concentrations in cord blood ranged from 30 to 130% of the maternal concentrations (Liu et al, 2011, Kim et al 2011a, Gützkow et al 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many PFAAs, which are highly resistant to degradation and are environmentally persistent (Conder et al, 2008), have been widely used in commercial and industrial products (Renner, 2001). Because of their wide industrial application and common global use in consumer products in recent decades, PFAAs have been detected in the liver, fat, and serum of wildlife (De Silva and Mabury, 2006), and in human serum and blood (Kannan et al, 2004), breast milk (Kärrman et al, 2006), and umbilical cord blood (Apelberg et al, 2007). Perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) both dominate in human serum (Lau et al, 2004) and a number of PFSAs and PFCAs of varying chain length (C4-C14) have also been detected in human body fluids, though at lower levels (Olsen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[52] A large cross-sectional study involving the analysis of 293 samples of cord blood from Baltimore, Maryland, USA, compared PFOS and PFOA levels to birth outcomes of gestational age, birthweight, birth length, head circumference and ponderal index and showed negative associations between concentrations of PFOS and PFOA and ponderal index. [53] Maternal blood concentrations of PFOA, but not PFOS, were negatively associated with birthweight in newborns from Denmark. [54] A further study reported a statistically significant negative correlation between abdominal circumference and maternal PFOA, a statistically significant positive association between ponderal index to maternal PFOA of women who were obese before pregnancy, and a statistically non-significant negative correlation between head circumference and maternal PFOA.…”
Section: Human Exposure Pathways and Need For Epidemiologic Studiesmentioning
confidence: 89%